Self-control in a criminal sample: A comparison of sex offenders and non-sex offenders. - Doering, Shawna Cleary (My University, 2002)
The purpose of this study was to determine whether the criminal histories and analogous behaviors of three inmate samples (non-sex offenders, in-treatment sex offenders, and never treated sex offenders) would reflect the predictions of Gottfredson and Hirschi in their General Theory of Crime. This study utilized survey questionnaires and interviews to explore the relationships of abusive parenting to criminal history and analogous behaviors in both the two samples of sex offenders and the non-sex offender sample. In addition, the role of opportunity and routine activities in sex offenders' victim selection was addressed through in-depth interviews. This study found moderate support for the self-control assertion that offenders do not specialize. In particular, evidence was found in interviews with sex offenders that supported the generality of deviance. However, the survey data suggested that the in-treatment sex offenders differed from the other two samples in levels of self-control. Furthermore, mixed results were found for the relationship between low self-control and engaging in analogous and criminal behaviors among the three groups. The in-depth interviews did support the role of opportunity in sex offenders' victim selection through their physical proximity to victims and/or their knowledge of victims' emotional availability. Additionally, support was found for Cohen and Felson's Routine Activities Theory in the sexual offending of the respondents in this study, suggesting that available targets and lack of guardianship play an important role in victim selection.
Keywords: Gottfredson, Michael R. General theory of crime.; Sex offenders Psychology.; Sociology, Criminology and Penology.; Self-control.